RETRO EXPERIENCE OF CHARITY AND PATRONAGE SUPPORT FOR THE ESTABLISHMENT OF HIGHER EDUCATION INSTITUTIONS IN UKRAINE - Kirdan, Olena (Mountain School of Ukrainian Carpaty, 2023)
The actualization of research on the problem of charitable and philanthropic support for the formation of higher education institutions of Ukraine is due to the fact that constructive retro-experience has prospects for use for the post-war recovery and development of modern institutions of higher education in Ukraine. The purpose of the study is to analyze the experience of charitable and philanthropic support for the establishment of higher education institutions in Ukraine at the beginning of the 19th century. Research methods. Achieving the goal of the article made it possible to use the methods of analysis, synthesis, comparison, concretization and generalization. The article specifies the main approaches to interpreting the concepts of «charity», «charitable activity», «patronage», «patronage activity». Based on the analysis of dissertations and scientific publications, it was established that the establishment of higher education institutions in Ukraine at the beginning of the 19th century took place with significant charitable and philanthropic support from broad sections of the population: nobles, craftsmen, former Cossacks, and peasants. It manifested itself in the provision of funds for the opening of higher education institutions, the transfer of material assets and land allotments, etc., which significantly supplemented budget funding. The value of the experience of charitable and philanthropic support for the formation and development of the system of higher education in Ukraine in the first half of the 19th century is indicated, since philanthropists were the initiators and sponsors of the opening of most universities, higher women's courses, lyceums and schools (gymnasiums) of higher sciences, and philanthropic support for the opening and development of universities and institutions of higher professional education in Ukraine in the 19th century became a common phenomenon.